CONFRONTING THE THREAT OF RELATIVISM: Views from Islamic Philosophy - Moh. Nasrin Nasir (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2011)
Today the issue of ethics and most importantly moral values are being seen as merely based upon opinions and emotions. This has led towards a relativisation of moral values and thus towards the erosion of values amongst societies. This paper would analyze and suggest ways of preserving values for the structuring of developmental ideas for thinkers in developing countries. Coming from an Islamic standpoint the ideas of virtues have to be rooted within the transcendent or the Absolute. Such defense of virtues are defi nitely beyond the grasp of usual western philosophy as the philosophy that is propagated by Islam is not a mere intellectual exercise but a transformative exercise which connects the profane to the sacred, the outer to the inner and the physical world to the spiritual world. The loci or the focus point is the human being thus developing the idea of being human via the inculcation of and preservation of virtues is of utmost importance. The virtues most important in Islam such as justice, moderation or temperance have been discussed by various muslim philosophers. These virtues are rooted in the Absolute and through His presence in the various levels of existences are they known. For Using ideas from malay cosmology and soteriology based upon the writings of Malay scholars, this paper would highlight ways to preserve and ensure Malay society does not fall under the threat of relativism of moral values.